Unraveling Deterioration in the Quality of Philippine Education - Gumarang Jr., Bernardo K.; Gumarang , Brigitte K. (Future Science / FSH-PH Publications, 2021)
Education has a great role on the growth and development of economy. It builds the young generation to become competent and future leaders of a country. It is observed by the Filipino people that there are problems in the Philippine education. This paper identified and discussed the problems occurred in the education system of the Philippines. A Literature review process was utilized by the researchers. The researchers also identified solutions on the problems being identified using the findings of the different studies. The result showed three major problems in the Philippine education system such as overcrowded students in a classroom, teacher are teaching subjects that is not their expertise, and poor quality in instruction. It is recommended that the Philippine Education must review their policies in hiring educators and address the needs of its stakeholders. These findings can be used as basis in creating policies to ensure quality in education.